Vascularized Lung Cancer Model for Evaluating the Promoted Transport of Anticancer Drugs and Immune Cells in an Engineered Tumor Microenvironment - Kim, Dasom; Hwang, Kyeong Seob; Seo, Eun U.; Seo, Suyeong; Lee, Byung Chul; Choi, Nakwon; Choi, Jonghoon; Kim, Hong Nam (Wiley-Blackwell, 2022)
The tumor microenvironment (TME) is the environment around the tumor, including blood vessels, immune cells, fibroblasts, signaling molecules, and the extracellular matrix (ECM). Owing to its component interactions, the TME influences tumor growth and drug delivery in a highly complex manner. Although several vascularized cancer models are developed to mimic the TME in vitro, these models cannot comprehensively reflect blood vessel-tumor spheroid interactions. Here, a method for inducing controlled tumor angiogenesis by engineering the microenvironment is presented. The interstitial flow direction regulates the direction of capillary sprouting, showing that angiogenesis occurs in the opposite direction of flow, while the existence of lung fibroblasts affects the continuity and lumen formation of sprouted capillaries. The vascularized tumor model shows enhanced delivery of anticancer drugs and immune cells to the tumor spheroids because of the perfusable vascular networks. The possibility of capillary embolism using anticancer drug-conjugated liquid metal nanoparticles is investigated using the vascularized tumor model. This vascularized tumor platform can aid in the development of effective anticancer drugs and cancer immunotherapy.